CO2 seawater acidification by CCS-simulated leakage: Kinetic modelling of Zn, Pb, Cd, Ni, Cr, Cu and As release from contaminated estuarine sediment using pH-static leaching tests. (November 2016) - Martín-Torre, M. Camino; Ruiz, Gema; Galán, Berta; Viguri, Javier R.
Graphical abstract: Highlights: Kinetic element release in a pH-static leaching test using CO2 for acidification. The model fits experimental release including the influence of Fe and other ions. Leaching simulation over time under acidic scenarios up to pH = 6. CO2 and HNO3 acidifications lead to different kinetics during element release. The generalised model proposed here is also useful for areas contaminated by iron. Abstract: A modified pH-dependent leaching test with continuous pH control that employed CO2 to acidify a seawater-sediment mixture is used to address Zn, Pb, Cd, Ni, Cr, Cu and As release from contaminated estuarine sediments under the influence of acidification processes. Long-term (480 h) leaching experiments at pH values of 7.0, 6.5 and 6.0 are performed. The different evolutionary patterns of the redox potential and Fe release at pH = 6 with respect to the other pH values shows the need to assess the influence of the initial Fe content in seawater upon elemental release. Hence, assays at pH = 6.0 are conducted using natural seawater with Fe concentrations between 9.02 and 153 μg/L. A set of in-series reactions for trace elements, Fe and other ions associated with Fe is proposed to model a Fe/multi-ion-dependent mechanism for trace metal release. The maximum concentration of each contaminant that can be released from the sediment and the kinetic parameters of the proposed model are completed for the studied pH values, for good consistency between the experimental and simulated mobilisation of each studied element.